Peran Manajemen Sumber Daya Manusia dalam Pentahelix: Systematic Literature Review - Sari Fitri (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The increasing complexity of contemporary development challenges requires a shift in human resource management toward collaborative models based on the pentahelix ecosystem, integrating government, academia, industry, media, and society. Previous studies have widely explored pentahelix applications across sectors; however, a clear conceptualization of the specific roles of each actor in human resource management remains limited. Using a Systematic Literature Review approach following the PRISMA framework, relevant publications indexed in Scopus and Sinta 2 from 2021–2025 were systematically identified and filtered, resulting in 16 core articles for in-depth analysis. The synthesis reveals that each pentahelix actor performs distinct yet interdependent roles in capacity development, knowledge transfer, and collaborative learning processes. Competency development operates through formal institutional mechanisms, experiential collaboration, and informal network-based interactions, while knowledge transfer occurs through codification, personalization, and socialization pathways. The effectiveness of collaboration is shaped by the interaction of contextual, structural, and relational factors within the ecosystem. The resulting conceptual framework highlights how integrated multi-stakeholder engagement accelerates sustainable capability development and provides a clearer theoretical foundation for designing collaborative human resource strategies. These findings offer both theoretical enrichment and practical guidance for policymakers and practitioners in strengthening ecosystem-based human resource development.